Creation, Christians and Environmental Stewardship - Gnanakan, Ken (Fronteira: Journal of Social, Technological and Environmental Science, 2015)
This article is based on a theoretical discussion between religion and environmentalism. The text aims to present a debate between the principles of Christianity and the theoretical discussions that are fundamental to today’s environmentalist vision. It leads to a theological and culturalism argument with general concepts of the environmental movement, particularly in Western culture. The author appropriates the theological debate, with biblical texts of the Old and New Testament as a source, in order to present Biblical principles of respect for nature. Dialoguing with the concepts used in environmental movements and anthropocentrism biocentrism, this paper seeks to support Christian principles of stewardship as a theocentric environmental proposal of the relationship between humans and nature. Keywords: Religion; Environmentalism; Stewardship; Environmental Theology.